Karakterisasi Fraksi Aktif Antioksidan dari Biji Gandaria (Bouea macrophylla) - Maidah Nopiana; Erica Mutiara Putri; Annastaya Novariyan; Iip Pahrudin; Candra Junaedi; Tarso Rudiana (ALCHEMY:Journal of Chemistry, 2023)
Gandaria (Bouea macrophylla) plants contain antioxidant compounds that can reduce free radicals. Free radicals are one of the causes of various degenerative diseases. The purpose of this study was to determine the fraction that had the highest antioxidant activity, and to determine the secondary metabolites contained in the most active fraction of B. macrophylla seeds based on LCMS/MS analysis. Maceration of B. macrophylla seeds with ethanol solvent. Ethanol maserate was concentrated and fractionated by liquid-liquid extraction method using n-hexane, ethyl acetate and ethanol as solvents. Antioxidant activity was measured by the free radical scavenger method with 1,1-diphenyl-2-picrylhidrazil as a source of radicals and characterization of the secondary metabolites contained in the most active fraction using a Liquid Chromatography-Mass Spectrometer. B. macrophylla seed ethanol extract has a % yield of 31.75%. The ethyl acetate fraction of B. macrophylla seeds has the highest mass compared to other fractions and has strong antioxidant activity with an IC50 value of 2.95 ppm. The ethyl acetate fraction of B. macrophylla seeds contains tannins, phenolic, flavonoid dan alkaloid compounds. Based on the results of the identification of secondary metabolites by LC-MS/MS, the ethyl acetate fractions of B. macrophylla seeds contained phenylalalnine compounds.